Global Study on Reconstruction of Public Live Markets, Slaughterhouses, and Meat Processing Facilities, Volume 2. Annexes - Nippon Koei (World Bank, Washington, DC, 2014)
This study used the data gathered during a previous World Bank project to assess the available options for the cost-effective reconstruction and rehabilitation of livestock market and slaughter facilities in the developing world. Using the rich array of resource material which the previous study gathered in five of the Bank's lending regions, this report provides information on the characteristics of these facilities. It assesses available technologies, processes and materials for reconstruction and makes recommendations on the appropriateness and cost-effectiveness of these measures under a variety of conditions. Despite the very serious state of disrepair and poor operating standards, there is much than can feasibly be done to improve outcomes in the near term and bring about better welfare, safety, and hygiene conditions for all parties concerned.